2012
DOI: 10.1007/s00590-012-1111-z
|View full text |Cite
|
Sign up to set email alerts
|

Knee sonography as a diagnostic test for medial meniscal tears in young patients

Abstract: Diagnostic studies-investigating a diagnostic test, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 12 publications
1
34
1
Order By: Relevance
“…23 Studies in human patients report sensitivities ranging from 30 to 100% and specificities ranging from 71.4 to 98% for sonographic diagnosis of meniscal pathology. [2][3][4][5][6]8,9,12,[15][16][17][18][19][20] The most recent studies report the highest sensitivities, specificities, and correct classification rates (CCRs), likely as a result of improvements in technology, training, and experience. Based on the recent results, the costs and availability, the portability of the equipment, and the safety associated with ultrasonography, the authors of these studies concluded that ultrasonography is a clinically useful diagnostic technique for meniscal pathology.…”
mentioning
confidence: 99%
“…23 Studies in human patients report sensitivities ranging from 30 to 100% and specificities ranging from 71.4 to 98% for sonographic diagnosis of meniscal pathology. [2][3][4][5][6]8,9,12,[15][16][17][18][19][20] The most recent studies report the highest sensitivities, specificities, and correct classification rates (CCRs), likely as a result of improvements in technology, training, and experience. Based on the recent results, the costs and availability, the portability of the equipment, and the safety associated with ultrasonography, the authors of these studies concluded that ultrasonography is a clinically useful diagnostic technique for meniscal pathology.…”
mentioning
confidence: 99%
“…The study showed high sensitivity and specificity values for ultrasound of 100% and 88.8% respectively in the age category above 30 years; 83.3% and 71.4% respectively in the age category below 30 years, concluding that ultrasound is a reliable method in suspected cases of medial meniscal injuries. [4] Another study by Park G-Y et al where ultrasound was performed on 22 patients and compared with MRI for the evaluation of meniscal tears. Results showed 29 meniscal tears on MRI out of which 25 were correctly diagnosed on ultrasound showing high sensitivity and specificity values of 86.2% and 84.9% respectively deducing that ultrasound is an effective imaging modality in diagnosing meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic imaging such as ultrasonography, MRI and weightbearing radiographs should not be used routinely. Although there are indications of a relatively high diagnostic accuracy of ultrasonography for diagnosing meniscal tears,71 ultrasound is limited because of its inability to evaluate the entire meniscus and other intra-articular pathology 12 72. Despite relatively high diagnostic accuracy,73 MRI should not be used routinely to diagnose a meniscal tear,12 as a previous study showed that 61% of subjects with a meniscal tear on MRI were asymptomatic during the previous month 7.…”
Section: Discussionmentioning
confidence: 99%